Triple gene mutations boost amylose and resistant starch content in rice: insights from sbe2b/sbe1/OE-Wxa mutants - Chen, Xiaoqiong; Guo, Qiaoling; Yang, Xiaoli; Yuan, Meng; Song, Jianguo; Fu, Hongyan; Zhang, Hongyu; Xu, Peizhou; Liao, Yongxiang; Ali, Asif; Du, Kangxi; Wu, Xianjun (Frontiers in Plant Science, 2024)
Previous studies have modified rice's resistant starch (RS) content by mutating single and double genes. These mutations include knocking out or reducing the expression of sbe1 or sbe2b genes, as well as overexpressing Wx a . However, the impact of triple mutant sbe2b/sbe1/OE-Wx a on RS contents remained unknown. Here, we constructed a double mutant with sbe2b/RNAi-sbe1, based on IR36ae with sbe2b, and a triple mutant with sbe2b/RNAi-sbe1/OE-Wx a , based on the double mutant. The results showed that the amylose and RS contents gradually increased with an increase in the number of mutated genes. The triple mutant exhibited the highest amylose and RS contents, with 41.92% and 4.63%, respectively, which were 2-and 5-fold higher than those of the wild type, which had 22.19% and 0.86%, respectively. All three mutants altered chain length and starch composition compared to the wild type. However, there was minimal difference observed among the mutants. The Wx a gene contributed to the improvement of 1000-grain weight and seed-setting rate, in addition to the highest amylose and RS contents. Thus, our study offers valuable insight for breeding rice cultivars with a higher RS content and yields.